SUATU STUDI TENTANG UJI HIDUP DIPERCEPAT TEGANGANBERTINGKAT: PERKEMBANGAN MUTAKHIR - Zanzawi Soejoeti (LPPM Universitas Terbuka, 2003)
This paper is reviewing the development of life testing data analysis of lie testing conducted in normal stress condition; stronger than normal stress (or constant stress accelerated life testing); and step stress accelerated life testing. It used exponential life test distribution model, log-normal accelerated model and tempered failure rate step stress model. It is completed by describing several problem for the future research.